Gross Hematuria and Hemolytic Anemia in Infectious Mononucleosis - Chinmayi Sharma; Navneet Venugopal; Shivaiah Balachandra (Case Reports in Pediatrics)
Introduction. Infectious mononucleosis (IM), caused by the Epstein–Barr virus (EBV), typically presents with fever, tonsillopharyngitis, and lymphadenopathy while rare, renal, and hematological complications such as gross hematuria and hemolytic anemia can occur, particularly in children. Case Presentation. We describe a 15-year-old male with infectious mononucleosis presenting with abdominal pain, sore throat, and red-colored urine for three days. Laboratory findings revealed leukocytosis, elevated liver enzymes, and hemoglobinuria. Serological testing confirmed EBV infection. Despite intravascular hemolysis, the patient’s anemia was mild, and he responded well to supportive care. Discussion. Gross hematuria and hemolytic anemia are uncommon in IM, with limited reports. Proposed mechanisms include viral-induced renal injury and autoimmune hemolysis. Differential diagnosis should consider other causes of hematuria, which can be differentiated through urine microscopy and serological tests. IM should be considered in patients with pharyngitis and hematuria, especially when other causes are excluded.